Correction: Marangi et al. Abundance of Human Pathogenic Microorganisms in the Halophyte Salicornia europaea L.: Influence of the Chemical Composition of Shoots and Soils. Agronomy 2024, 14, 2740 - Matteo Marangi; Sonia Szymanska; Kai-Uwe Eckhardt; Felix Beske; Gerald Jandl; Katarzyna Hrynkiewicz; Julien Pétillon; Christel Baum; Peter Leinweber (Agronomy)
In the original publication [...]